2005
DOI: 10.22358/jafs/67010/2005
|View full text |Cite
|
Sign up to set email alerts
|

Antioxidant status of lambs fed on diets supplemented with selenite or Se-yeast

Abstract: The effects of feed supplementation with inorganic and organic forms of selenium (Se) on the activities of blood glutathione peroxidase (GPx), superoxide dismutase (SOD) in erythrocytes as well as on total antioxidant status in plasma (TAS) were examined in lambs. Fifteen animals were divided into three groups and fed experimental diets for 3 months. The first group received the basic diet (BD) providing a daily intake 50.6 μg of Se only. Diets for the second and third groups consisted of BD supplemented with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
20
0

Year Published

2005
2005
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(22 citation statements)
references
References 20 publications
2
20
0
Order By: Relevance
“…Currently, about thirty Se-proteins have been indentified in mammals, but the physiological function of only less than half of them is well known. Among them, the best understood Se-Cys-protein appears to be cytosolic glutathione peroxidase, which functions as an antioxidant by removing reactive oxygen substances (Boldižárová et al, 2005). In agreement with the above, our recent studies revealed that dietary organic-Se or inorganicSe (Czauderna et al, 2004a) stimulated the accumulation of unsaturated fatty acids (UFA), conjugated linoleic acid (CLA) isomers in particular.…”
Section: Introductionsupporting
confidence: 63%
“…Currently, about thirty Se-proteins have been indentified in mammals, but the physiological function of only less than half of them is well known. Among them, the best understood Se-Cys-protein appears to be cytosolic glutathione peroxidase, which functions as an antioxidant by removing reactive oxygen substances (Boldižárová et al, 2005). In agreement with the above, our recent studies revealed that dietary organic-Se or inorganicSe (Czauderna et al, 2004a) stimulated the accumulation of unsaturated fatty acids (UFA), conjugated linoleic acid (CLA) isomers in particular.…”
Section: Introductionsupporting
confidence: 63%
“…On the basis of our results we may conclude that all forms of selenium applied increased the level of selenium in the blood of mothers and in the blood of kids, but we did not discover significant differences between the individual forms of selenium. Other authors also came to the conclusion that both the inorganic and organic form of selenium increased the selenium concentrations in the blood of lambs (Boldižárová et al, 2005), dairy cows (Juniper et al, 2006), and goats (Misurova et al, 2009a) in contrast to the control group. Leeson et al (2008) compared selenite, Se-enriched yeast, and B-Traxim Se in broilers and discovered that plasma concentrations of selenium did not differ significantly when using various forms of selenium.…”
Section: Discussionmentioning
confidence: 98%
“…Considering above, we suggest that dietary SeIV, especially H SeIV, has a pro-oxidant effect on the CLA isomers in the spleen. The pro-oxidative properties of sodium selenite are known from in vitro and in vivo experiments (Spallholz, 1997;Terada et al, 1999;Boldižárová et al, 2005). Consequently, the combined addition of CLAmix and H SeY to the diet showed a high but not significant increase of the concentration of c9t11CLA in the spleen (+27%) and blood plasma (+21%).…”
Section: Resultsmentioning
confidence: 97%
“…0.5 ppm Se as SeY) exhibited some pro-oxidative. It has been suggested that larger doses of dietary selenized yeast may lead to higher continuous release of selenomethionine from body deposits into the free amino acid pool with a subsequently higher production of H 2 Se, which has pro-oxidative properties (Boldižárová et al, 2005). PUFA mg/g n-6/n-3…”
Section: Resultsmentioning
confidence: 99%